Anti-biofilm and anti-quorum sensing activities of extract, fractions and compounds from the leaves of Cassia alata L. against yeast pathogens - Jean Paul Dzoyem; Simplice Chimi Fotso; Jean Duplex Wansi; Bellier Tabenkoueng; Willifred Dongmo Tekapi Tsopgni; Flavien Aristide Alfred Toze; Lyndy Joy McGaw (Elsevier, 2024)
Background: Cassia alata or Senna alata, also known as "ringworm bush" because of its very effective fungicidal properties, is commonly used in African traditional medicine to treat fungal infections. Despite extensive phytochemical and pharmacological studies previously reported on C. alata, the antibiofilm activity against pathogenic yeast as well as the related anti-quorum sensing mechanism of some active constituents has not yet been elucidated. The aim of the study was to isolate the bioactive constituents from the methanol extract of the leaves of C. alata (CAExt) using antibiofilm-guided fractionation against yeast fungal pathogens and then to investigate the anti-quorum sensing activity of the active constituents by assessing their ability to inhibit violacein production in Chromobacterium violaceum. Methods: Chromatographic methods were used to isolate the constituents of CAExt, and spectroscopic methods were used to elucidate the chemical structures of the isolated compounds. The broth microdilution assay was used to evaluate the antifungal activity against Candida albicans and C. parapsilosis, while crystal violet staining was used for the inhibition of biofilm formation and the disruption of preformed biofilm. The biosensor strain C. violaceum ATCC 12472 was used to investigate the anti-quorum sensing activity of the most active constituents. Results: The crude extract exhibited biofilm inhibition and eradication activities against the tested pathogenic yeast. The biofilm inhibition percentages ranged from 53.22 % to 75.38 %, while the biofilm eradication percentages ranged from 23.21 % to 64.25 %. The ethyl acetate fraction demonstrated high biofilm inhibition and eradication activities against the tested microorganisms. The biofilm inhibition percentages ranged from 58.19 % to 79.30 %, while the biofilm eradication percentages ranged from 34.105 % to 69.54 %. The purification of subfractions led to the identification of six compounds: stigmasterol (1), sitosterol (2), lupeol (3), emodin (4), kaempferol (5) and stigmasterol glycoside (6), two of which (4 and 5) showed potent biofilm inhibition and eradication activities. Both compounds demonstrated significantly lower MBIC50 values of 70.81 µg/mL and 65.65 µg/mL against Candida albicans and MBEC50 values of 63.65 µg/mL and 82.66, respectively, against C. albicans and C. parapsilosis. The crude extract and compounds (4) and (5) also demonstrated quorum sensing inhibitory activity, as indicated by the MQSIC value of 1024 µg/mL for the crude extract and 128 µg/mL for the two compounds. Moreover, compounds (4) and (5) displayed significant inhibitory effects on violacein production, as indicated by their low IC50 values of 28.08 µg/mL and 26.44 µg/mL, respectively. Conclusions: Data obtained in this study not only support the traditional use of C. alata in the treatment of fungal infections but also reveal C. alata extract, as well as the two isolated bioactive compounds emodin (4) and kaempferol (5), as a potential source for developing antibiofilm alternative agents against biofilm-associated yeast infections. List of compounds studied: stigmasterol (1), sitosterol (2), lupeol (3), emodin (4), kaempferol (5), stigmasterol glycoside (6)